2019
DOI: 10.3390/s19173662
|View full text |Cite
|
Sign up to set email alerts
|

Can We Use Satellite-Based FAPAR to Detect Drought?

Abstract: Drought in Australia has widespread impacts on agriculture and ecosystems. Satellite-based Fraction of Absorbed Photosynthetically Active Radiation (FAPAR) has great potential to monitor and assess drought impacts on vegetation greenness and health. Various FAPAR products based on satellite observations have been generated and made available to the public. However, differences remain among these datasets due to different retrieval methodologies and assumptions. The Quality Assurance for Essential Climate Varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Monthly products at 0.5 • × 0.5 • between SeaWiFS and QA4ECV were also benchmarked, and we demonstrated that a monthly linear correction can be used for correcting the entire QA4ECV time series, from 1982 onwards, for correcting the stability performance. Recently, Giering, et al (2019) proposed a framework to establish fundamental satellite data series for climate applications [52]. Here, we applied a simple approach that can bring a solution for merging different sensor products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monthly products at 0.5 • × 0.5 • between SeaWiFS and QA4ECV were also benchmarked, and we demonstrated that a monthly linear correction can be used for correcting the entire QA4ECV time series, from 1982 onwards, for correcting the stability performance. Recently, Giering, et al (2019) proposed a framework to establish fundamental satellite data series for climate applications [52]. Here, we applied a simple approach that can bring a solution for merging different sensor products.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of terrestrial surfaces thus concern a large number of users in such applications including agriculture, forestry, environmental monitoring, etc. [8][9][10]. Since plant canopies significantly affect the spectral and directional reflectance of solar radiation, the analysis of these reflectances leads to a better understanding of fundamental processes controlling the biosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Rojas et al, 2011;Vicente-Serrano et al, 2013Törnros and Menzel, 2014). The Global Inventory Monitoring and Modeling System (GIMMS) NDVI was generated based on Advanced Very-High-Resolution Radiometer (AVHRR) observations and has accounted for various deleterious effects, such as orbital drift, calibration loss and volcanic eruptions (Beck et al, 2011;Pinzon and Tucker, 2014). For the current study, the latest version of GIMMS NDVI (3g.v1) was used, which covers the time period from 1981 to 2015 at biweekly temporal resolution and 8 km spatial resolution (Pinzon and Tucker, 2014).…”
Section: Gimms Ndvimentioning
confidence: 99%
“…Impacts include crop failure, food shortage, famine, epidemics and even mass migration (Wilhite et al, 2007;Ding et al, 2011;Zhou et al, 2018). In recent years, severe events have occurred across the world, such as the 2003 central Europe drought (García-Herrera et al, 2010), the 2010 Russian drought (Spinoni et al, 2015), the 2011 Horn of Africa drought (Nicholson, 2014), the 2000 drought in southeastern Australia (van Dijk et al, 2013;Peng et al, 2019c), the 2013-2014 California drought (Swain et al, 2014), the 2014 North China drought (Wang and He, 2015) and the 2015-2017 southern Africa drought (Baudoin et al, 2017;Muller, 2018). Widespread negative effects of these droughts on natural and socioeconomic systems have been reported afterwards (Wegren, 2011;Arpe et al, 2012;Griffin and Anchukaitis, 2014;Mann and Gleick, 2015;Dadson et al, 2019;Marvel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The EVI index of the Moderate-resolution Imaging Spectroradiometer (MODIS) was used in Germany in 2018 to identify potential regional differences in order to examine drought effects in various land cover types [19]. The Fraction of Absorbed Photosynthetically Active Radiation (FAPAR) can reflect the greenness and health conditions of vegetation and has been used to monitor and assess the impact of drought [20]. In particular, FAPAR has been chosen and operationally used in the formula of the Combined Drought Indicator (CDI) for monitoring drought in the European Drought Observatory (EDO) within the Copernicus Emergency Management Service [21].…”
Section: Introductionmentioning
confidence: 99%